A gas breathing hydrogen/air biofuel cell comprising a redox polymer/hydrogenase-based bioanode. Issue 1 (December 2018) - Szczesny, Julian; Marković, Nikola; Conzuelo, Felipe; Zacarias, Sónia; Pereira, Inês; Lubitz, Wolfgang; Plumeré, Nicolas; Schuhmann, Wolfgang; Ruff, Adrian
Abstract Hydrogen is one of the most promising alternatives for fossil fuels. However, the power output of hydrogen/oxygen fuel cells is often restricted by mass transport limitations of the substrate. Here, we present a dual-gas breathing H2 /air biofuel cell that overcomes these limitations. The cell is equipped with a hydrogen-oxidizing redox polymer/hydrogenase gas-breathing bioanode and an oxygen-reducing bilirubin oxidase gas-breathing biocathode (operated in a direct electron transfer regime). The bioanode consists of a two layer system with a redox polymer-based adhesion layer and an active, redox polymer/hydrogenase top layer. The redox polymers protect the biocatalyst from high potentials and oxygen damage. The bioanodes show remarkable current densities of up to 8 mA cm-2 . A maximum power density of 3.6 mW cm-2 at 0.7 V and an open circuit voltage of up to 1.13 V were achieved in biofuel cell tests, representing outstanding values for a device that is based on a redox polymer-based hydrogenase bioanode. Hydrogen is an attractive alternative fuel, but many hydrogen-conversion electrocatalysts contain expensive materials. Here the authors report a dual-gas breathing hydrogen/air biofuel cell comprised of a modified polymer/hydrogenase bioanode and a bilirubin oxidase biocathode, delivering improved output.